Offshore teaching in chronic disease management: The Monash-Shenzhen experience. Issue 1 (1st February 2018) - Piterman, Leon; Yang, Hui; Blashki, Grant
Abstract : The important role of GPs and the high prevalence and burden of chronic disease in China have been discussed in other articles in this series, so there is no need to reiterate this background here. This article deals with the pedagogy of chronic disease management as presented to cohorts of Chinese GPs from Shenzhen attending an offshore program at Monash University in Australia. The program, which commenced in 2010, was 7 weeks in duration and has now expanded to 13 weeks, enabling greater coverage of important topics, more site visits, and instruction in teaching and research methods, along with development of research proposals often based on management of a chronic disease. Significance statement: Since 2010, groups of GPs from Shenzhen have been trained at Monash University in Melbourne, Australia, as part of an agreement with the Government of Shenzhen to train GP leaders. This article describes the history and scope of the program. More than 200 physicians have now participated in the program, which currently consists of 13 weeks of offshore experiential learning in Melbourne. As we confront the epidemic of chronic noncommunicable disease, in addition to clinical training with a strong emphasis on systems of care for patients with chronic disease, the Shenzhen physicians receive research training and are expected to implement projects in their clinics in Shenzhen designed to improve the care of patients with chronic physical or mental illness.